Clinical and Radiological Follow-Up of a Pfizer-BioNTech COVID-19 Vaccine-Induced Hemichorea-Hemiballismus. Issue 1 (18th May 2022) - Batot, Cédric; Chea, Maryane; Zeidan, Sinead; Mongin, Marie; Pop, Gabriel; Mazoyer, Julie; Degos, Bertrand
Background: Hemichorea-hemiballismus is a rare hyperkinetic movement disorder. Case Report: A 90-year-old male developed left hemichorea-hemiballismus after his second dose of the Pfizer-BioNTech COVID-19 vaccine. A wide range of investigations including magnetic resonance imaging did not reveal an alternative cause. [18F]-fluorodeoxyglucose-positron emission tomography (FDG-PET) showed increases in right putamen fixation compared to the left side. The patient showed significant improvement after five days of intravenous corticosteroids, with a normal FDG-PET. Discussion: This hemichorea-hemiballismus case shows dynamic restoration of putamen metabolism mirroring clinical evolution after administration of corticosteroids, suggesting an autoimmune COVID-19 vaccine-induced reaction.